PENGARUH KUALITAS LAYANAN BANDARA TERHADAP CITRA PERUSAHAAN BANDARA: (SURVEI PADA BANDARA KLIA2 MALAYSIA) - Gugyh Susandy; Angelia Anggia Permata Norman; Dinda Rahma Aulia (STIESA Press, 2022)
This research at to verify the effect of airport service quality on and airports' corporate image. Based on the existing literature, a structural model was proposed considering the suggested relationship between such constructs. Based on this model, a survey was elaborated through an electronic questionnaire, all Stie.Sutaatmadja Students who use airports being the target population. A total of 102 respondents who declared use of airports was obtained. The results showed that airport service quality can influence the corporate image of airports. Extending the existing literature, which was limited to investigate services provided only by airlines, there was also evidence that the influence of the con structs analyzed applies not only to services provided by airlines, but also to services in airport terminals. The findings lead to the conclusion that it is relevant that managers and administrators of airport terminals ensure the quality of services provided on the ground. The guarantee of such quality can influence directly and indirectly the corporate image of airports, even enabling the preservation of the government concession to operate the airport.